Oxygen and mitochondrial inhibitors modulate both monomeric and heteromeric TASK-1 and TASK-3 channels in mouse carotid body type-1 cells. - Turner, P; Buckler, K (2013)
In rat arterial chemoreceptors, background potassium channels play an important role in maintaining resting membrane potential and promoting depolarization and excitation in response to hypoxia or acidosis. It has been suggested that these channels are a heterodimer of TASK-1 and TASK-3 based on their similarity to heterologously expressed TASK-1/3 fusion proteins. In this study, we sought to confirm the identity of these channels through germline ablation of Task-1 (Kcnk3) and Task-3 (Kcnk9) in mice. Background K-channels were abundant in carotid body type-1 cells from wild-type mice and comparable to those previously described in rat type-1 cells with a main conductance state of 33 pS. This channel was absent from both Task-1(-/-) and Task-3(-/-) cells. In its place we observed a larger (38 pS) K(+)-channel in Task-1(-/-) cells and a smaller (18 pS) K(+)-channel in Task-3(-/-) cells. None of these channels were observed in Task-1(-/-)/Task-3(-/-) double knock-out mice. We therefore conclude that the predominant background K-channel in wild-type mice is a TASK-1/TASK-3 heterodimer, whereas that in Task-1(-/-) mice is TASK-3 and, conversely, that in Task-3(-/-) mice is TASK-1. All three forms of TASK channel in type-1 cells were inhibited by hypoxia, cyanide and the uncoupler FCCP, but the greatest sensitivity was seen in TASK-1 and TASK-1/TASK-3 channels. In summary, the background K-channel in type-1 cells is predominantly a TASK-1/TASK-3 heterodimer. Although both TASK-1 and TASK-3 are able to couple to the oxygen and metabolism sensing pathways present in type-1 cells, channels containing TASK-1 appear to be more sensitive.